Explicating the Influence of Entrepreneurial Orientation on Access to Land and Economic Performance - Ayoyimika A. OMOLADE; Olaleke O. OGUNNAIKE; Ebe E. IGBINOBA; Mary Ejiehi EZEMA (Communications of International Proceedings, 2021)
Land is essential for food production and can be used as collateral or to generate income. Women’s economic performance is tied to her access to land and property. However, gender equality exists in accessing productive resources like land. Despite various land empowerment programmes women still own less than 20 per cent of global land and the quality of such land is lower than those owned by men. Also, even though women represent more than half of Africa’s population they only contribute 39% of Africa’s GDP. However, past studies reveal that entrepreneurial orientation is a solution to challenges faced by businesses aiming to attain performance. Using desktop review approach on existing literature. This study tends to investigate the moderating role of entrepreneurial orientation on access to land for economic performance of farms in Nigeria. This study is hinged on entrepreneurial Mindset Theory. This study concludes that if female farmers have more autonomy, is more proactive, innovative and show more competitive aggressiveness with existing access to land, their farm output, profit and sales will increase leading to greater economic performance.
Keywords: Access to land; Autonomy; Competitive Aggressiveness; EconomicPerformance; Female Farmers; Innovative; Women Empowerment; Proactiveness.